A Multicenter Study of Real-world Practice for Management of Abnormal Liver Function Tests in Children with Acute Infectious Diseases - Lee, Yoon; Yi, Dae Yong; Lee, Yoo Min; Choi, So Yoon; Choi, You Jin; Lee, Kyung Jae (Journal of Korean medical science, 2021)
Abnormal liver function tests (LFTs) are commonly seen in pediatric patients with acute infectious diseases. Few studies and no definite clinical guidelines for these conditions are available. The present study aimed to elucidate the causes and factors associated with prolongation of liver enzyme elevation. We also investigated actual real-world practices in Korea. A retrospective study was performed on all patients younger than 18 years, who visited six tertiary teaching hospitals around Korea in 2018 for acute infectious diseases and showed alanine aminotransferase (ALT) levels above 60 IU/L without other specific conditions that could cause ALT elevation. We categorized the infections that cause LFT elevation into six groups: respiratory infection, gastrointestinal infection, urinary tract infection, other febrile disease, Epstein-Barr virus infection, and cytomegalovirus infection. We collected data on the medical specialty of the attending physician who followed up the subject, follow-up duration, percentage of follow-up loss, and their investigation. A total of 613 patients were enrolled in this study, half of whom (50.7%) were younger than 12 months. The mean initial aspartate aminotransferase and ALT values were 171.2 ± 274.1 and 194.9 ± 316.1 IU/L (range 23-2,881, 60-2,949 IU/L), respectively; however, other LFTs were within the normal range. Respiratory infection was the most common diagnosis (45.0%), and rhinovirus was the most commonly identified pathogen (9.8%). The follow-up rate was higher with pediatric gastroenterologists (90.5%) and non-gastroenterology pediatricians (76.4%) than with pediatric residents and emergency doctors. Older age was related to better ALT recovery (odds ratio [OR] of age for month = 1.003; 95% confidence interval [CI], 1.001-1.004; = 0.004), while the number of infection episodes (OR = 0.626; 95% CI, 0.505-0.777; < 0.001) was associated with poor ALT recovery. Abdominal sonography was the most commonly used diagnostic tool (36.9%), followed by the hepatotropic virus workup. The modalities of hepatitis workup were significantly differently applied by physicians based on their specialties and institutions. Abnormal liver function test after a systemic infection was common in respiratory infection and under the age of 1 year. Age, number of infections, and initial results of LFTs were related to ALT recovery time. Inter-physician, inter-institution, and inter-specialty variances were observed in real-world practice.